Shooting Skills As Part Of The Psychomotor Learning Of Students - Dini Restuti; Nurul Ihsan; Bafirman Bafirman; Aldo Naza Putra; Wilda Welis (STKIP Singkawang, 2025)
Petanque is a precision sport that has gained popularity, especially among adolescent to adult athletes. One of the most challenging skills to master in petanque is the shooting technique, which requires optimal hand-eye coordination, concentration, and anthropometric factors such as arm length. This study aims to examine the influence of arm length, hand-eye coordination, and concentration on the shooting ability of petanque athletes in West Sumatra. This quantitative study employed a path analysis approach. The research was conducted in February 2025 at the Sports Field of the Faculty of Sports Science, Padang State University. The population consisted of all 40 petanque athletes from West Sumatra, selected using a total sampling technique. Data collection instruments included an arm length test, a tennis ball throw-and-catch test (hand-eye coordination), the Grid Concentration Test, and a petanque shooting test. Data were analyzed using structural equation modeling at a significance level of α = 0.05. The findings revealed that: (1) arm length had a direct and significant effect of 6.30% on shooting ability; (2) hand-eye coordination had a direct and significant effect of 20.9%; (3) concentration had a direct and significant effect of 8.53%; (4) arm length had an indirect effect of 12.18% through concentration; (5) hand-eye coordination had an indirect effect of 31.14% through concentration; and (6) collectively, arm length, hand-eye coordination, and concentration had a significant combined effect of 44.89% on the shooting ability of West Sumatran petanque athletes